Knowledge and Factors Influencing Self-care Behaviors of Arteriovenous Fistula among CKD Patients in Hemodialysis Units in the Jaffna Peninsula - Appuhamy, K.D.S.M.; Kaushalya, L.S.; Jegapragash, V.; Thangaraja, B.R. (University of Jaffna, 2024)
Chronic Kidney Disease (CKD) is a non-communicable disease, which causes progressive kidney damage and serious complications. Hemodialysis is a management method currently used worldwide to reduce or control symptoms related to CKD. Prior to the hemodialysis treatment, a proper vascular access such as Arteriovenous fistula (AV Fistula) is needed to maintain blood flow throughout the treatment. There is a lack of contemporary data on knowledge and factors on self-care behaviors on arteriovenous fistula among CKD patients who have undergone Hemodialysis in the Jaffna peninsula in Sri Lanka. The general objective of this study is to assess the knowledge and factors influencing self-care behaviors of Arteriovenous Fistula among CKD patients in hemodialysis units in the Jaffna Peninsula. Descriptive cross-sectional study was done among 155 registered CKD patients in Hemodialysis units in the Teaching Hospital Jaffna, the Base Hospital Thelippalai, the Base Hospital Chawakachchei and the Base Hospital Point Pedro in the Jaffna Peninsula. All registered patients with CKD who had undergone hemodialysis with permanent AV Fistula, over 12 years old age were included as the sample and patients with psychiatric disorders with communication barriers were excluded from the study. The study found that 68.9% of patients had adequate knowledge of self-care behaviors of AV Fistula and the rest ( 31.1% ) of the patients belonged to the inadequate knowledge category. Finally, the results revealed that attending regular follow-up clinics were significantly associated with knowledge of self-care behavior Av fistula among CKD patients who have undergone hemodialysis.
Keywords: Chronic kidney disease; Arterio-venous fistula; Hemodialysis; Self-care behaviors